Gertrude Stein and the Reinvention of Rhetoric - Kirsch, Sharon J. (Book collections on Project MUSE., 2014)
Gertrude Stein is recognized as an iconic and canonical literary modernist. In Gertrude Stein and the Reinvention of Rhetoric, Sharon J. Kirsch broadens our understanding of Stein' s influence to include her impact on the field of rhetoric. For humanities scholars as well as popular audiences, the relationship between rhetoric and literature remains vexed, in part due to rhetoric' s contemporary affiliation with composition, which makes it separate from, if not subordinate to, the study of literature. Gertrude Stein recognized no such separation, and this.